LEGAL CONSTRAINTS ON THE PERVERSE USE OF TECHNOLOGY: THE CASE OF ANTIPERSONNEL LAND MINES (NATIONAL CAPITAL LAW JOURNAL, 1999)
NA
Keywords: International Humanitarian Law; Anti-Personnel Land Mines; Human Rights; Right To Life; Armed Conflict; Geneva Conventions; Ottawa Landmine Convention; Certain Conventional Weapons Convention; Crime Against Humanity; Mine Clearance And Disarmament.